1999
DOI: 10.1111/j.1365-2141.1999.01323.x
|View full text |Cite
|
Sign up to set email alerts
|

Diversity of leukaemic cell morphology in ATL correlates with prognostic factors, aberrant immunophenotype and defective HTLV‐1 genotype

Abstract: Summary.To investigate the diversity of morphology in adult T-cell leukaemia/lymphoma (ATL) and its possible association with the pathophysiology of ATL, we selected 36 acute cases and 14 chronic cases phenotypically confirmed to have >90% ATL cells in peripheral blood mononuclear cells. Prototype ATL cells were observed in all cases, although the percentage of all lymphoid cells varied considerably (48·9 Ϯ 23·8 in acute type, 29·6 Ϯ 18·9 in chronic type; P ¼ 0·015). Chronic lymphocytic leukaemia (CLL)-like mo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
27
0

Year Published

2001
2001
2017
2017

Publication Types

Select...
5
4
1

Relationship

2
8

Authors

Journals

citations
Cited by 41 publications
(27 citation statements)
references
References 20 publications
0
27
0
Order By: Relevance
“…4,5 A further category of lymphocytes with 'unusual morphology', including lymphoblasts and lymphocytes with features including cytoplasmic granulation and vacuolation, has been described in ATLL. 6 The classification study reported 62.8% 4-year survival for smoldering ATLL. In another retrospective study, 11 of 26 (42%) smoldering ATLL transformed to aggressive ATLL after a median of 81 months.…”
Section: Introductionmentioning
confidence: 99%
“…4,5 A further category of lymphocytes with 'unusual morphology', including lymphoblasts and lymphocytes with features including cytoplasmic granulation and vacuolation, has been described in ATLL. 6 The classification study reported 62.8% 4-year survival for smoldering ATLL. In another retrospective study, 11 of 26 (42%) smoldering ATLL transformed to aggressive ATLL after a median of 81 months.…”
Section: Introductionmentioning
confidence: 99%
“…Hyperlobated nuclei may be rare or absent in some cases, with small, uniform, CLL-like cells seen more commonly in the chronic or smoldering form of the disease. 392 The bone marrow is frequently normocellular with minimal and focal interstitial or diffuse involvement seen in approximately half of cases. 391,393 This bone marrow involvement is usually non-paratrabecular and may be subtle even with extensive peripheral blood involvement.…”
Section: Adult T-cell Leukemia/lymphomamentioning
confidence: 99%
“…These cells are considered pathognomonic of ATL and enable diagnosis alone. 44 Other atypical cells may have the following morphologies: chronic lymphocytic leukemia, lymphoblastic type, and pleomorphic with granular or vacuolar cytoplasm. 44 Flow cytometry is an important test for the diagnosis of ATL.…”
Section: Physical Examination Useful In Selected Casesmentioning
confidence: 99%